Value of APACHE II, SOFA and CardShock scoring as predictive tools for cardiogenic shock: A single‐centre pilot study - Małgorzata Chlabicz; Wojciech Łaguna; Remigiusz Kazimierczyk; Ewelina Kazimierczyk; Paulina Łopatowska; Monika Gil; Bożena Sobkowicz; Karol A. Kamiński; Agnieszka Tycińska (ESC Heart Failure)
Abstract Aims The aim of this study was to determine the value of the Acute Physiology and Chronic Health Evaluation II (APACHE II), Sequential Organ Failure Assessment (SOFA) and CardShock scoring systems in predicting the risk of in‐hospital, 30 day and 3 year mortality in patients with cardiogenic shock (CS). Methods This was a single‐centre observational study conducted between May 2016 and December 2017. Data from consecutive patients with CS admitted to the intensive cardiac care unit (ICCU) were included in the analysis. Results The study group comprised 63 patients with CS {median age 71.0 [interquartile range (IQR), 59–82]; 42 men}: 32 patients with ischaemic and 31 with non‐ischaemic aetiology. The median APACHE II, SOFA and CardShock scores were 13 (IQR, 9.9–19.0) points, 8.0 (IQR, 6.0–10.0) points and 3.0 (IQR, 2.0–5.0) points, respectively. The in‐hospital, 30 day and 3 year mortality rates were 39.7%, 41.3% and 77.8%, respectively. APACHE II and SOFA scores were significantly higher in the group of patients who died at 30 days (P = 0.043 and P = 0.045, respectively). The CardShock score was higher in patients with CS who died in hospital (P = 0.007) and within 30 days (P = 0.004). No score was statistically significant for 3 year mortality. Area under the curve (AUC) analysis showed that the CardShock score had the highest value in predicting in‐hospital and 30 day mortality relative to APACHE II and SOFA, with a cut‐off score of 5 points [AUC: 0.70; 95% confidence interval (CI): 0.59–0.81; P = 0.001] and 4 points (AUC: 0.71; 95% CI: 0.60–0.82; P < 0.001), respectively. The Bayesian Weibull model demonstrated the utility of all scales in estimating short‐term risk in patients with CS, with the impact of APACHE II and SOFA on patient life expectancy decreasing to a non‐significant level at approximately 32 days and CardShock at 33 days. The forest plots derived from the Bayesian logistic regression analysis show significant estimated coefficients with 94% highest density interval (HDI) for in‐hospital and 30 day mortality. The use of invasive or non‐invasive ventilation, a higher heart rate and a less negative fluid balance showed an unfavourable prognosis. Survival was associated with being in the pre‐CS class, with a higher glomerular filtration rate and a higher platelet count. Conclusions APACHE II and SOFA could be used for the risk stratification of patients with CS admitted to the ICCU. CardShock proved to be a more appropriate tool for assessing short‐term prognosis in patients with CS of all aetiologies, suggesting that there is potential for its promotion for use in daily clinical practice.